Complex Systems Design &Amp; Management 2015
DOI: 10.1007/978-3-319-26109-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance as a Cornerstone for the Application of Regeneration Paradigm in Systems Lifecycle

Abstract: The circular economy is an economy, firstly, considering the natural resources as finite and the nonexistence of waste, secondly, assimilating the industrial system as a natural system and, finally, emphasizing the paradigm of regeneration. Nevertheless, this paradigm is not clearly defined and this paper aims to found it by proposing solutions to its implementation in the industrial world. The proposal is based on a comparison between the natural system and the industrial system by using the trophic organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…For this, the circular economy is based on the following schools of thought: (i) Biomimicry (Benyus, 2009), study of nature to design goods and to develop new technologies; (ii) Industrial Ecology (Despeisse et al, 2012), study of the material and energy flow through the industrial system to add value to waste produced by a firm; (iii) Cradle-to-Cradle (McDonough and Braungart, 2010), design of goods in harmony with environment and communities through the term "nutrients". In our previous works (Diez et al, 2015), we propose an approach of these concepts through the notion of "regeneration paradigm". The regeneration term comes from the food web that is circular and reuses all that is produced by each entity being a part of trophic organization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this, the circular economy is based on the following schools of thought: (i) Biomimicry (Benyus, 2009), study of nature to design goods and to develop new technologies; (ii) Industrial Ecology (Despeisse et al, 2012), study of the material and energy flow through the industrial system to add value to waste produced by a firm; (iii) Cradle-to-Cradle (McDonough and Braungart, 2010), design of goods in harmony with environment and communities through the term "nutrients". In our previous works (Diez et al, 2015), we propose an approach of these concepts through the notion of "regeneration paradigm". The regeneration term comes from the food web that is circular and reuses all that is produced by each entity being a part of trophic organization.…”
Section: Introductionmentioning
confidence: 99%
“…This cycle is repeated indefinitely and regulates itself. In (Diez et al, 2015), we have shown that by applying the same principles to the industrial world, it is necessary to add processes to play the role of decomposers, called "technical decomposers" or "decomposition processes". Unlike to the industrial ecology where companies exchange their waste to use them like resources, the technical decomposers transform unusable items to add them value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors use the term of nutrients to talk about resources. (Diez et al, 2015) have approached this notion. These schools of thought are oriented design and consider a perfect exchange of wastes between different firms.…”
Section: Introductionmentioning
confidence: 99%
“…L'état d'un composant permet de décider le cycle (i.e. maintenance, réutilisation, régénération, recyclage de sa matière ou retour à l'écosphère (Diez et al, 2015)) dans lequel le composant peut être réintroduit et donc impacter de manière non linéaire son prix de revente. Cette décision nécessite alors une quantification de la capacité de l'élément, i.e.…”
Section: Introductionunclassified